Mercy in a Conflictual Society: An Inward Journey Towards Reconciliation (Hekima Review, 2016)
Today’s world is confronted with serious religious and social challenges despite her advancement in technology and communication. All the efforts of human mediation in reconciliation fail to restore and heal fully the wounds of people. The Holy Father has declared a year of Mercy to help Christian to meditate and reflect on the mercy of God in human history. This paper looks at the year of mercy in a conflictual arena especially in the continent of Africa. After discussing and analysing the challenges of fully living this year of mercy, it tackles the aspect of inward reconciliation as an alternative to fulfill fruitfully a process of reconciliation. Arguably the confessional reconciliation has to consider primarily the inward reconciliation which is rooted and understood as God’s grace